Management of tracheobronchial foreign body in children - Cataneo, Antonio José Maria [UNESP]; Cataneo, Daniele Cristina [UNESP]; Ruiz, Raul Lopes [UNESP] (Springer, 2008)
To study cases of foreign bodies (FB) in the tracheobronchial tree investigating the clinical and radiological FB characteristics, complications and endoscopic and surgical intervention. Medical and radiological records review of all FB aspiration cases treated at S (a) over tilde uo Paulo State University Hospital over the last 30 years. One hundred and sixty-four FB cases were analyzed; 57% were male, 84% of these were under 16 years old. The most common clinical manifestations were coughing (68.3%) and choking (54.9%). The most common FBs were seeds (peanut, bean, maize) and also small metal or plastic objects. Radiography was normal in 21.3%, atelectasis was present in 40.9%, hyperinsufflation in 17.1% and the FB was radio-opaque in 20.7%. FB time in the bronchial tree varied from hours to years. The most serious complications, as fibroatelectasis and difficult resolution pneumonia, were caused by the long time that the FB remained in the bronchial tree. FB extraction was by endoscopy in 89% of cases, while 6% required surgical extraction or resection of destroyed part of lung, and 5% spontaneously eliminated the FB. There was no mortality in this series. Coughing and choking were the commonest clinical findings. Most FBs were dried seeds. Complications were due to delays in diagnosis, and most would not have existed if the doctor had given credence to the history. Radiography can be normal as most FBs are radiotransparent. FB extraction was by endoscopy, but a few cases required surgery and others were spontaneously eliminated.
Keywords: foreign bodies; aspiration; bronchoscopy; child; radiology